Gender Differences in Basketball's Impact on Fitness for Students. - Saptono, Tri; Sumintarsih; Mustofa, Hanafi (SHS Web of Conferences, 2025)
Research Objectives: 1) To Assess The Impact Of Basketball On The Enhancement Of Physical Fitness In Male Students. 2) To Evaluate How Basketball Influences Physical Fitness Improvement In Female Students. 3) To Examine The Differences In The Effects Of Basketball On Physical Fitness Between Male And Female Students. The Study Employed An Experimental Method. The Research Population Consisted Of Students From The Upn "Veteran" Yogyakarta's Communication Science Study Program Who Were Enrolled In The Sports Ii Basketball Course. Data Analysis Was Conducted Using The T-Test, Following Prerequisite Tests For Normality And Homogeneity. Research Findings: 1) Male Students Showed An Average Improvement Of 2.625 In Physical Fitness Due To Basketball. 2) Female Students Demonstrated A Greater Average Improvement Of 4.68 In Physical Fitness. 3) The Difference In Physical Fitness Improvement Between Male And Female Students Was 2.061.